KESIAPSIAGAAN MASYARAKAT KABUPATEN BENER MERIAH TERHADAP ANCAMAN LETUSAN GUNUNG API BURNI TELONG - Nurul Izzati; Agussabti; Indra (J-Innovation, 2018)
Volcano preparedness is a response or an attempt to provide protection to ourselves and the environment, both material and non-material. In the volcanic region of Bur Ni Telong, Bener Meriah District, the lack of preparedness of communities, a high level of mobility and building in the wrong place at the identified disaster-prone areas is the biggest cause of vulnerability in the region endures the fire. The research for preparedness of Bur Ni Telong Communities is a blend of quantitative and qualitative methods. Further calculation results are analyzed and the summarized into a proposed strategy for achieving community preparedness for disasters. The results showed that the overall level of preparedness or communities in the central highlands area of study especially in the category of less ready with a cumulative index score 48.506. Unpreparedness is influenced by a number of factors, such as knowledge, attitudes, early warning system, employment and education. Some possible strategies proposed to improve community preparedness in the study area is to focus activities to reduce the risks, empowering communities as subjects not objects in disaster management, and local document of knowledge through educational curriculum in schools.